2009
DOI: 10.1016/j.matchemphys.2009.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Cure kinetics of vapor grown carbon nanofiber (VGCNF) modified epoxy resin suspensions and fracture toughness of their resulting nanocomposites

Abstract: a b s t r a c tIn this study, the cure kinetics of Cycom 977-20, an aerospace grade toughened epoxy resin, and its suspensions containing various amounts (1, 3 and 5 wt.%) of vapor grown carbon nanofibers (VGCNFs) with and without chemical treatment were monitored via dynamic and isothermal dynamic scanning calorimetry (DSC) measurements. For this purpose, VGCNFs were first oxidized in nitric acid and then functionalized with 3-glycidoxypropyltrimethoxy silane (GPTMS) coupling agent. Fourier transform infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The influence of carbonbased nano-fillers on the enthalpies of the epoxy cure reaction is different for different nanocomposites. The addition of CNTs [19,20,31] and EG [24] decreased the "H of epoxy, whereas CNF had no pronounced effect on the heat of the TGDDM/DDS cure reaction [32] and silanized and polyaniline modified CNFs increased the "H of epoxy [33,34]. It is believed that the addition of hydroxyl-containing compounds (water, alcohols, phenols, acids) considerably promoted the interaction of epoxy compounds with amines and other nucleophilic reagents [35].…”
Section: Effects Of Gos On the Cure Reactionmentioning
confidence: 99%
“…The influence of carbonbased nano-fillers on the enthalpies of the epoxy cure reaction is different for different nanocomposites. The addition of CNTs [19,20,31] and EG [24] decreased the "H of epoxy, whereas CNF had no pronounced effect on the heat of the TGDDM/DDS cure reaction [32] and silanized and polyaniline modified CNFs increased the "H of epoxy [33,34]. It is believed that the addition of hydroxyl-containing compounds (water, alcohols, phenols, acids) considerably promoted the interaction of epoxy compounds with amines and other nucleophilic reagents [35].…”
Section: Effects Of Gos On the Cure Reactionmentioning
confidence: 99%
“…In addition, CNF has been applied as the toughening filler of the structural material for resin based composites. (Seyhan et al, 2009) reported that the addition of low content of silanized vapor grown carbon nanofiber (VGCNF) improved the fracture toughness of the epoxy resin by about 12%. They concluded that attachment of epoxide end groups containing silane molecules to surfaces of CNF enhanced the compatibility between CNF and epoxy.…”
Section: Concepts Of Nano-scale Reinforcement and Toughness In Thermomentioning
confidence: 99%
“…[11][12][13] In addition, many studies concerning the effects of carbon nanostructures on mechanical and fracture behaviour of thermosetting polymers had reported a notable change in fracture resistance of nanocomposites with lower filler contents in comparison with silica or clay. [14][15][16][17][18] Modification of polymer matrices with graphene platelets (GPs) as reinforcement has opened a new path towards manufacturing advanced materials. 19,20 A GP consists of several single graphene layers with a usual stack thickness around 3 to 80 nm.…”
Section: Introductionmentioning
confidence: 99%